Zakat for the Elderly: A Survey of Mustahiks and An Islamic Law Perspective - Fahlefi, Rizal; Alimin, Alimin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2020)
The study aims to find out a general description of mustahiks of old-age insurance program from National Zakat Agency (BAZNAS) of Tanah Datar Regency and to analyse the legal status of the program from Islamic law perspective. The old-age insurance program is distribution of consumptive zakat permanently throughout life for the elderly. The researcher used a survey method. The results showed that the old-age insurance program is directed to meet the basic needs of elderly mustahiks. The characteristics of the elderly mustahiks are as follows: 90% are women, 45% are classified as the old-old, 50% have never attended school, 60% are sick, 85% are non-potential elderly people, 55% live in unworthy shelter, 65% live alone, before receiving zakat 80% meet their needs with the help of others, 80% have no income other than zakat. These facts support that the consumptive zakat for the elderly must be continued, because it greatly helps elderly welfare. Although there is no specific argument regarding zakat for the elderly, it doesn’t contradict the provisions of Islamic law. If the Caliphs Abu Bakr, Umar, and 'Ali decided on a policy of providing compensation for non-Muslim elderly from Baitul Mâl, for Muslim elderly ofcourse even more important. Penelitian ini bertujuan untuk mengetahui gambaran umum dari mustahik program jaminan hari tua dari Badan Amil Zakat Nasional (BAZNAS) Kabupaten Tanah Datar dan untuk menganalisis status hukum program perspektif hukum Islam. Program jaminan hari tua merupakan penyaluran zakat konsumtif secara permanen bagi lansia sepanjang hidupnya. Peneliti menggunakan metode survei. Hasil penelitian menunjukkan bahwa program jaminan hari tua bertujuan untuk memenuhi kebutuhan dasar para mustahik lansia. Karakteristik mustahik lansia tersebut adalah sebagai berikut: 90% diantaranya adalah perempuan, 45% diklasifikasikan sebagai lansia berumur sangat lanjut, 50% tidak pernah bersekolah, 60% dalam kondisi sakit, 85% merupakan lansia yang tidak potensial, 55% tinggal di tempat tinggal yang tidak layak, 65% tinggal sendirian, sebelum menerima zakat 80% memenuhi kebutuhan mereka dengan mengandalkan bantuan orang lain, 80% tidak memiliki penghasilan selain zakat. Fakta-fakta ini mendukung bahwa program zakat konsumtif untuk lansia mesti dilanjutkan, karena sangat membantu kesejahteraan lansia. Meskipun tidak ada dalil khusus tentang alokasi zakat untuk lansia, tetapi hal tersebut tidak bertentangan dengan ketentuan hukum Islam. Jika Khalifah Abu Bakr, Umar, dan ‘Ali pernah mengambil kebijakan untuk memberikan santunan kepada lansia non-Muslim dari Baitul Mâl, maka menyantuni lansia Muslim tentu lebih utama lagi.